# Prove Using induction

Let, $$<a_n>_{n \ge 0}$$ be a sequence with $$a_0 = 0,a_1=1,$$ and $$a_n=2a_{n-1}+a_{n-2}, \forall n \ge 2.$$ Prove that,for every $$m > 0$$ and $$0\leq j \leq m,2a_m \mid (a_{m+j}+(-1)^j a_{m-j}).$$

Note by Tarit Goswami
8 months, 3 weeks ago

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold
- bulleted- list
• bulleted
• list
1. numbered2. list
1. numbered
2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in $$...$$ or $...$ to ensure proper formatting.
2 \times 3 $$2 \times 3$$
2^{34} $$2^{34}$$
a_{i-1} $$a_{i-1}$$
\frac{2}{3} $$\frac{2}{3}$$
\sqrt{2} $$\sqrt{2}$$
\sum_{i=1}^3 $$\sum_{i=1}^3$$
\sin \theta $$\sin \theta$$
\boxed{123} $$\boxed{123}$$

Sort by:

Induct on $$j.$$ For $$j=0,1,$$ $$a_{m+j}+(-1)^j a_{m-j} = 2a_m,$$ so it's clear. Now if $$j \ge 2,$$ write \begin{align} a_{m+j}+(-1)^j a_{m-j} &= 2a_{m+j-1} + a_{m+j-2} + (-1)^j (a_{m-j+2} - 2 a_{m-j+1} ) \\ &= 2\left(a_{m+j-1} - (-1)^j a_{m-(j-1)} \right) + \left( a_{m+j-2} + (-1)^j a_{m-(j-2)} \right) \\ &= 2 \left( a_{m+j-1} + (-1)^{j-1} a_{m-(j-1)} \right) + \left( a_{m+j-2} + (-1)^{j-2} a_{m-(j-2)} \right) \\ \end{align} and both the terms in the parentheses are divisible by $$2a_m,$$ by the inductive hypothesis.

- 8 months, 2 weeks ago

Are you sure you want that $$2$$ there? I mean, this is never true for $$j=1$$ since $$a_{m+1}+(-1)^1 a_{m-1} = a_m,$$ which is not divisible by $$2a_m.$$

- 8 months, 2 weeks ago

Yes , it is 2* a_m ..Ooh! sorry there was a typo in recurrence relation i have fixed it .

- 8 months, 2 weeks ago